Modifikasi Alat Ripstix Fiberglass untuk Pembelajaran PJOK - Agustina, Rininta; Puspodari; Kholis, Moh. Nur (SPRINTER: Jurnal Ilmu Olahraga, 2024)
This research aims to explore the impact of utilizing fiberglass ripstix equipment on students' motivation to learn rhythmic gymnastics. The The Research and Development (R&D) methodology used in this study is based on the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. research participants were fourth-grade students from SDN Betet 3, SDN Ngletih 1, and SDN Banaran 2 in Kediri City. To evaluate the appropriateness of the media., Validation tests were carried out by three specialists: a material expert, a media expert, and a practitioner expert. The study also featured a small-scale trial with 10 students and a large-scale trial involving 40 students. The results of the study are as follows: (1) The material validation received a score of 81.25%, classified as Very Appropriate; the media validation scored 90%, which is also categorized as Very Appropriate; and the practitioner validation reached 95%, indicating it is Very Appropriate. (2) In the trials, the small-scale trial at SDN Betet 3 scored 91.33%, the large-scale trial conducted at SDN Ngletih 1 achieved a score of 91.73%, and the large-scale trial at SDN Banaran 2 scored 89.87%. All these results fall under the Very Feasible category. (3) It was concluded that fiberglass ripstix media is highly suitable for use in PJOK learning without requiring any modifications.